La inclusión de las personas con discapacidad en los acuerdos de paz de Colombia - Biel-Portero, Israel; Hernández-Silva, Romel Armando (Iberoamerican Journal of Development Studies, 2019)
There is a noteworthy relationship between disability and armed conflict. The critical situations of violence, besides causing new-fangled disabilities, may intensify the existing ones. Taking into consideration that the term «disability» is a human rights issue as well as the high quantity of victims of the conflict who in fact have any sort of disability, it could have been significant that the Colombian peace agreement with FARC-EP has encompassed a specific disability approach. Therefore, the absence of this perspective may perpetuate its exclusion. Throughout the current negotiation process with ELN, an opportunity is opened to mend this omission.